Jordanian Youth in Collective Action: Structure and Significance of the Jordanian Al-?ir?k Al-Shab?b? (Youth Movement) - BLANCO-PALENCIA, María (Revista de Estudios Internacionales Mediterráneos, 2015)
Increased and widespread regional collective action in the Middle East and North Africa (MENA) during the recent Arab revolutions reflects the existence of a marked change in the structure and the strategies used by young organised activists. This period has witnessed greater organisation efforts from young actors, taking the role of leaders and organisers, which have resulted in a variety of social movements that pursue strategies different from former ones. I argue that, in Jordan, the Jordanian Al-?ir?k Ash-Shab?b? (Youth Movement) represents this new regional trend of youth-led, youth-organised, informal, uninstitutionalized, horizontal, network-like organization that is re-defining what dissent looks like in the country today. In the case of Jordan, the role of youth has been widely understudied, resulting in an incomplete interpretation of this revolutionary period in Jordan. The aim of this paper is to contribute to this gap of knowledge, analysing the movement’s appearance and organisation to present its overall socio-political characteristics. Keywords Organisation, Strategy, Collective action, Youth, Arab spring, Jordan Resumen "La juventud jordana en acción colectiva: estructura y significado del movimiento juvenil Al-?ir?k Al-Shab?b? " El aumento y la expansión de la acción colectiva en Oriente Medio y el Norte de África durante las recientes revoluciones árabes, reflejan la existencia de un cambio significativo en la estructura y las estrategias empleadas por activistas jóvenes organizados. Este periodo se ha caracterizado por un mayor esfuerzo organizativo por parte de los jóvenes, que han adoptado el papel de líderes y organizadores, resultando en una variedad de movimientos sociales que ponen en marcha estrategias diferentes a las que se empleaban con anterioridad. En Jordania, Al-?ir?k Ash-Shab?b? (Movimiento de Jóvenes) representa esta nueva tendencia regional —movimientos liderados y organizados por jóvenes, de carácter informal y no institucional, y organizados como una red horizontal no jerarquizada— que está redefiniendo la disidencia hoy. En el caso de Jordania, el papel de los jóvenes no ha sido estudiado en profundidad, lo que ha resultado en una interpretación incompleta de este periodo revolucionario en Jordania. Este artículo tiene como objetivo reducir esta brecha de conocimiento, analizando la aparición y organización del movimiento, presentando sus características socio-políticas principales. Palabras clave Organización, Estrategia, Acción colectiva, Juventud, Primavera árabe, Jordania